The Evaluation of Sunnah and Non-Sunnah Eating Manners among Young Muslim Generation and Their Effects on Comfort Practices and Satiety Level Case Study in Kuantan, Pahang - Ibrahim Abu Bakar; Rafidah Ab Rahim (USIM Press, 2024)
Vol 6. No. 1 (June 2021)